Effects of stereotactic radiofrequency thermocoagulation in the globus pallidus internus on refractory tic disorders. (1st January 2020) - Li, Yu-Hui; Zhao, Kai; Wang, Mei-Qing; Wang, Jing; Gao, Bu-Lang
Abstract: Objective: To investigate the effect of stereotactic radiofrequency thermocoagulation in the globus pallidus internus on refractory tic disorders. Materials and methods: Forty patients with refractory tic disorders were enrolled between January 2015 and July 2017 to experience stereotactic radiofrequency thermocoagulation in the globus pallidus internus. All clinical data, Yale Global Tic Severity Scale (YGTSS) scores, serum dopamine (SDA), and 5-hydroxytryptamine (5-HT) were analyzed. Results: Radiofrequency thermocoagulation was successfully performed in all patients. Periprocedural complications occurred in two patients (5.0%), one with fever (2.5%) and one with a urination disorder (2.5%); both returned to normal after treatment. After 12 months of follow-ups, excellent improvement was exhibited in 18 patients (45.0%), marked improvement in 10 (25.0%), good improvement in 9 (22.5%), and invalid in 3 (7.5%), with a total efficacy rate of 92.5% (37/40). Twenty-eight patients (70%) showed excellent or marked improvement without additional treatment after surgery. YGTSS scores were significantly ( p  < 0.05) decreased after compared with before thermocoagulation. SDA was significantly ( p  < 0.05) decreased 6 months (80.78 ± 18.82 ng/ml) and 12 months (75.65 ± 15.23 ng/ml) after compared with before (125.63 ± 35.26 ng/ml) surgery, whereas 5-HT was significantly ( p  < 0.05) increased 6 months (58.93 ± 16.88 ng/ml) and 12 months (62.63 ± 15.21 ng/ml) after compared with before (35.62 ± 3.41 ng/ml) surgery. Conclusion: Stereotactic radiofrequency thermocoagulation can be safely applied in the globus pallidus internus to treat refractory tic disorders, resulting in significant tic symptom relief and a decrease in SDA but increase in 5-HT.